Fitness parameters in young football players are affected by training load and somatic-anthropometric variations - Schillaci, G.; Ivaldi, M. (Sport Sciences for Health, 2023)
Purpose This study aimed at investigating relationship between variations in fitness parameters, variations in somatic-anthropometric parameters and training load variables in Italian elite soccer players during pre/mid and post-puberty.